ЕКСПРЕСІЯ ГЕНІВ ЛЕГКИХ ЛАНЦЮГІВ ІМУНОГЛОБУЛІНІВ В СТЕРЕОТИПНИХ ВИПАДКАХ В УКРАЇНСЬКІЙ КОГОРТІ ХВОРИХ НА ХРОНІЧНУ ЛІМФОЦИТАРНУ ЛЕЙКЕМІЮ - ABRAMENKO, I.; BILOUS, N.; MARTINA, Z.; DYAGIL, I.; CHUMAK, A. (PH Akademperiodyka, 2024)
Background. Analysis of immunoglobulin heavy chain gene (IGHV) rearrangements expressed in chronic lymphocytic leukemia (CLL) cells has provided insights into the B-cell receptor (BCR) repertoire in CLL. In more than 40% of CLL patients, (quasi)identical or stereotyped BCR is expressed. The recent data point at the non-stochastic expression of immunoglobulin light lambda (IGLV) or kappa (IGKV) chains as well. Several pairs of IGHV and IGK/LV have been described for some major stereotyped subsets, but most subsets have not been characterized. Aim. To study the IGK/LV gene expression in stereotyped CLL cases. Materials and Methods. Analysis was performed in a group of 105 CLL patients with stereotyped BCR. The cases with stereotyped BCRs were identified according to Agathangelidis et al. (2021). The IGHV and IGK/LV gene expressions were studied by a polymerase chain reaction followed by direct sequencing. Results. The expression of the IGK/LV genes in the most presented major stereotyped subsets (#1, #2, #3C3, #4, #6, #28а) was in agreement with the data reported by other authors. For the cases of subsets #5b, #9D1, #9D4, #16, #50, #59, and #77, differences were found. The new data on the IGK/LV gene expression in 55 minor clusters were presented. A number of patterns of the IGK/LV gene expression depending on the phylogenetic clan and mutational status of the IGHV genes have been described. Conclusion. The non-stochastic distribution of the IGKV/LV gene expression in the individual stereotyped subsets was confirmed. Taking into account the complementary role of the light chains in antigen recognition by the clonotypic BCRs, it was suggested that the subsets with the heterogeneous IGK/LV expression might be reclassified and divided into separate subgroups based on the IGHV and IGK/LV association.